Investigation of the production and antifungal properties of nanocapsules containing chamomile essential oil - Tianjiao Liu; Xinyao Qu; Mojiao Zhao; Dafang Zhang; Jianpeng Guo (Scientific Reports)
Abstract Our study aims to investigate the production of nanocapsules containing chamomile essential oil and assess their antifungal properties. We have developed a technological process for producing nanocapsules, selected chamomile raw materials, extracted the essential oil, and conducted research on the antimicrobial activity of nanocapsules against four fungal cultures: Candida albicans CGMCC 2.538, Aspergillus fumigatus CGMCC 3.5925, Trichophyton rubrum CGMCC 3.3777 and Epidermophyton floccosum CGMCC 3.3722. Our research revealed significant antimicrobial activity of chamomile-containing nanocapsules against all tested fungi. The zones of fungal inhibition varied depending on the oil concentration and were statistically significant (P < 0.05). The obtained results hold practical significance for the development of antimicrobial agents based on plant oils in the treatment of fungal infections. Further research may focus on the molecular mechanisms of chamomile oil’s action, clinical trials in humans, and the optimization of nanocapsule formulations. These steps may contribute to the development of more effective and targeted antimicrobial agents for combating fungal infections and improving patient health.